2006
DOI: 10.1038/nmeth973
|View full text |Cite
|
Sign up to set email alerts
|

Targeted chromosome elimination from ES-somatic hybrid cells

Abstract: To engineer a stem cell genome, we developed a technology for targeted elimination of chromosomes from mouse embryonic stem (ES)-somatic hybrid cells. Here we demonstrate the use of a universal chromosome elimination cassette (CEC) for elimination of a single embryonic stem cell (ESC)-derived chromosome 11 or 12, and also both copies of chromosome 6, which harbor pluripotency-associated genes including Nanog. We attribute hybrid-cell pluripotency to the expression of Nanog from the reprogrammed somatic-cell nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
5

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 8 publications
2
64
0
5
Order By: Relevance
“…Thus, we expected that two copies of endogenous Nanog mRNA might not be sufficient to make the tetraploid cells pluripotent during the initial full cell cycles after cell fusion with somatic cells when extrinsic Nanog was fully reprogrammed. We addressed this question by attempting the complete elimination of two copies of mouse ES cell-derived Nanog-bearing chromosome 6s in ES cell-somatic cell hybrid cells (Matsumura et al, 2007). The results clearly demonstrated that Nanog expression from reprogrammed somatic genomes could efficiently maintain pluripotency in mouse ES cell-somatic cell hybrid cells, but that at least three out of four copies of chromosome 6s were required to keep tetraploid cells pluripotent.…”
Section: Epigenetic Reprogramming Potencies In Mouse Es Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, we expected that two copies of endogenous Nanog mRNA might not be sufficient to make the tetraploid cells pluripotent during the initial full cell cycles after cell fusion with somatic cells when extrinsic Nanog was fully reprogrammed. We addressed this question by attempting the complete elimination of two copies of mouse ES cell-derived Nanog-bearing chromosome 6s in ES cell-somatic cell hybrid cells (Matsumura et al, 2007). The results clearly demonstrated that Nanog expression from reprogrammed somatic genomes could efficiently maintain pluripotency in mouse ES cell-somatic cell hybrid cells, but that at least three out of four copies of chromosome 6s were required to keep tetraploid cells pluripotent.…”
Section: Epigenetic Reprogramming Potencies In Mouse Es Cellsmentioning
confidence: 99%
“…The subsequent cell divisions yield an accumulation of cells exhibiting targeted chromosomal loss (Lewandoski & Martin, 1997) ( Figure 1B). We have developed CEC plasmid vectors containing a pair of loxP sites in an inverted orientation, which reproducibly induced hemizygous or homozyous loss of CECtagged chromosomes (Matsumura et al, 2007;Otsuji et al, 2008). To isolate transformants of CEC, a ubiquitously expressed drug-resistant gene and a green fluorescent protein (GFP) reporter gene were inserted in the into the Cre-inverted loxP sequence.…”
Section: Cre-inverted Loxp Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Enucleation of ES cells before fusion may not be practicable in circumventing this problem as it has been revealed to eliminate the ability of the remaining ES cytoplast to re-activate expression of pluripotency markers in hybrids with somatic cells (50). The selective deletion of chromosomes is possible but may be impracticable for the complete set of chromosomes (51). Alternatively, ES cells-derived chromosomes carrying the major histocompatibilty complex loci could be removed selectively to avoid or at least reduce rejection reactions during treatment.…”
Section: Somatic Cell Fusion With Embryonic Stem Cellmentioning
confidence: 99%
“…Jedoch ist die Tetraploidie der resultierenden fusionierten Zellen ein großes Hindernis für ihre mögliche medizinische Anwendung. Zwar gibt es bereits erste Ansätze, um einzelne Chromosomen aus den Zellen zu entfernen [31], doch bedarf es neuer Methoden, um die Zellen vollständig vom ES-Zellgenom zu befreien. Die Reprogrammierungsaktivität von ES-Zellen findet sich im Kern [32].…”
Section: Transkriptionsfaktorenunclassified